2022
DOI: 10.3390/machines10080714
|View full text |Cite
|
Sign up to set email alerts
|

Pick–and–Place Trajectory Planning and Robust Adaptive Fuzzy Tracking Control for Cable–Based Gangue–Sorting Robots with Model Uncertainties and External Disturbances

Abstract: A suspended cable−based parallel robot (CBPR) composed of four cables and an end−grab is employed in a pick−and−place operation of moving target gangues (MTGs) with different shapes, sizes, and masses. This paper focuses on two special problems of pick−and−place trajectory planning and trajectory tracking control of the cable−based gangue−sorting robot in the operation space. First, the kinematic and dynamic models for the cable−based gangue−sorting robots are presented in the presence of model uncertainties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Since D, E, F, and G are the functions of φ, it is sure that a and b are also the functions of φ, that is, a � a(φ) and b � b(φ) from equations ( 21) and (23). Hence, A, B, and C are also the functions of φ, that is, A � A(φ), B � B(φ), and C � C(φ) in equation (5).…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Since D, E, F, and G are the functions of φ, it is sure that a and b are also the functions of φ, that is, a � a(φ) and b � b(φ) from equations ( 21) and (23). Hence, A, B, and C are also the functions of φ, that is, A � A(φ), B � B(φ), and C � C(φ) in equation (5).…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Te pick-and-place trajectory of the robot was constructed using NURBS curves. Liu et al [23] proposed four-phase pick-and-place trajectory planning scheme based on the S-shaped acceleration/deceleration algorithm and quintic polynomial trajectory planning method of the cable-based gangue-sorting robot in the operation space.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure for generating a trajectory can be approached by several mathematical and analytical or computational and numerical methodologies, but all with the same objective of determining a set of points or descriptive function of a path taking into account the parameterizations [22]. Relevant and recent research on trajectory planning for industrial robots can be observed in [23], [24], [25] and [26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the integration of robots in gangue and foreign matter screening has gained significant momentum as a notable development trend. Researchers have shown considerable interest in the visual information-based gangue robot selection method [1][2][3]. The efficacy of a gangue selection robot, which relies on visual information, is contingent upon precise gangue and foreign object recognition, as well as the speed of the manipulator.…”
Section: Introductionmentioning
confidence: 99%